Postoperative muscle mass restoration as a prognostic factor in patients with resected pancreatic cancer - Lee, Jongchan (PLoS One, 2020)
BACKGROUND: Recent studies have found that muscle depletion may be a prognostic predictor in patients with pancreatic cancer (PC). However, in these studies, limited data were used to assess the relationship between the serial change in body composition and outcomes after PC resection. Hence, we evaluated the changes in body composition during the perioperative period in patients with PC and their association with the overall survival (OS). METHODS: A total of 89 patients with PC who received surgery with curative intent between 2006 and 2015 were included in this study retrospectively. These patients underwent serial computed tomography (CT) scans: preoperatively, immediately after surgery (4 weeks), and 12 and 24 weeks after resection. The muscle and visceral fat areas were measured at the third lumbar vertebra level on cross-sectional CT images using sliceOmatic V5.0 program (TomoVision, Canada). The body composition ratio was determined by dividing the post-resection body composition at each point (4, 12, and 24 weeks) by the pre-resection body composition. Patients were divided into two groups—higher and lower groups—based on this body composition ratio (skeletal muscle mass ratio [SMR], visceral fat mass ratio [VFR]). The OS was compared between the two groups using the log-rank test. RESULTS: The median age of patients was 63 (27–84) years, and the baseline body mass index was 23.0 (17.0–35.8) kg/m(2). In the comparison of the SMR, there was no significant difference in the OS between the two groups at 4 and 12 weeks (4 weeks, P = 0.488; 12 weeks, P = 0.397). However, the higher group showed a longer OS than the lower group at 24 weeks (39 vs. 20 months, P = 0.008). Similarly, in the VFR, there was no significant difference in the OS between the two groups at 4 and 12 weeks (4 weeks, P = 0.732; 12 weeks, P = 0.060). However, the OS was longer in the higher group at 24 weeks (35 vs. 22 months, P = 0.023). When we analyzed the effect of muscle restoration at 24 weeks after resection on the OS by gender, there was no significant difference between the OS and SMR in the male group (P = 0.213), but a significant difference was noted in the female group (P = 0.002). In the multivariate Cox regression analysis, the SMR at 24 weeks after resection was significantly associated with the OS (P = 0.023) but not VFR at 24 weeks. In 69 patients without recurrence at 6 months, the SMR at 24 weeks was related to longer OS but without statistical significance (P = 0.07). CONCLUSIONS: This study suggests that the restoration of muscle mass at 24 weeks after resection may be an independent prognostic factor for survival in patients with resected PC.